Lessons from the South. Issue 1 (April 2015) - Chambers, Iain
<x xml:space="preserve">Abstract</x> Iain Chambers' essay challenges explanations of the Arab Spring emerging from the Occidental media, arguing that the terms of engagement set by the Arab revolts can no longer be unilaterally defined by the West. Chambers stresses the centrality of the Mediterranean as an increasingly evident site of confluence between East and West and between North and South. He goes on to argue that the events of the Arab Spring reopen the Western cultural and political lexicon, and put into question the historical alliance between Christianity and the universalising discourses of modernity. Ideas regarding the individual, the public sphere, political agency, religion, secularism and the state are necessarily being renegotiated in the context of the uprisings. The lived experiences of the Arab Spring slip beyond Western constructions of the events to expose the political and cultural burden of a modernity that may no longer be determined or managed single-handedly by the West. The Arab uprisings have occurred in the same time frame as protests in several European capitals, particularly since the fiscal collapse of 2008, and while there are distinct differences in these social unrests there is also, Chambers observes, a common factor: the rejection of the hypocrisies of the modern state. The new perspectives emerging from this confluence of experience around the shores of the Mediterranean may yield a more radical humanism within social, cultural, and political formations that are not automatically circumscribed by the global dictates of neoliberalism.